Advanced Development of a Prayer Schedule Bot Application on Telegram Using PHP - Sofran Bahrurozi; Asroni Asroni; Cahya Damarjati (Universitas Muhammadiyah Yogyakarta, 2020)
A bot is a web robot or an assistant with computer intelligence. The usefulness of a bot is very much starting from the web, messenger, and others. One application possessing a provider to make a bot is a Telegram. The development of technology, such as social media applications, has made them prevalent for the public, including most Muslims. Sometimes, people will be negligent in worshiping when using the application. Therefore, creating a prayer schedule bot is necessary to prevent people from doing so. A framework creation aimed to facilitate the stages of making a bot using a PHP programming language. The bot-making results could be utilized in various countries with the calculation method found in a bot, providing a preference for users. Telegram bot is preferred for smartphone users wanting storage efficiency and having an internet connection. In contrast, the conventional prayer scheduler application does not care much about the storage taken and does not have an internet connection.